Aprendizado baseado em jogos para o ensino de conceitos básicos de mecânica newtoniana - Dittmann, Rafael Augusto Ferreira (2024)
This work presents the development and implementation of a digital educational game called "Newton’s Guide,"created to facilitate the teaching of Newtonian mechanics in an engaging way. Developed on the Unreal Engine 5 platform using the engine’s Blueprint Visual Scripting and C++ programming language, the game offers an immersive experience set in the 17th century, where the main character, guided by the teachings of Isaac Newton, learns and applies physics concepts to overcome obstacles. This project aims to contribute to the fields of education and technology by demonstrating that educational games are an effective pedagogical strategy for teaching Newtonian mechanics, making it easier to understand the concepts and sparking students’ interest in the subject.